Representation of Depression Sufferers in Short Films Using 360⁰ Virtual Reality - Al Hafiz, Ahmad; Rustim; Pratama, Ferli Mulianto (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Mental disorders, especially depression, are becoming increasingly common in society, but are often underestimated because they are not physically visible. Depression is characterized by deep sadness, loss of hope, helplessness, difficulty concentrating, and even thoughts of suicide. This phenomenon inspired the creation of Kecil?, an experimental fiction work based on 360⁰ Virtual Reality (VR), which aims to convey the emotional experiences of people with depression in an immersive way. The film tells the story of an individual who personifies his internal conflicts through imaginary characters, depicting an inner struggle related to existential questions about birth, life, and death. The film creation process was carried out systematically through the stages of development, preproduction, production, and post-production, including idea development, visual observation, concept design, location selection, casting, controlled improvisation staging, lighting arrangements, and shooting using the point of view (POV) technique with an Insta360 X3 camera. The post-production stage involves editing long takes and using visual effects such as Content-Aware Fill and Masking to maintain visual continuity and enhance the film's aesthetics. The results of the study show that Kecil? successfully represents the emotional experiences of people with depression in depth. The careful use of mise-en-scène, cinematography, lighting, sound, and staging allows the audience to feel the main character's cathartic process and understand the complexity of the feelings of individuals with depression. The 360⁰ VR approach increases audience engagement directly, opens up space for dialogue, reduces stigma, and emphasizes the importance of community support for mental health. This film proves that film media can be an effective educational tool and mental health campaign, highlighting that mental health issues, though seemingly minor, have a significant impact if ignored.